The effectiveness of SSI-based digital science book on Jetis Sidoarjo batik waste to improving higher order thinking skills - Ria Wulandari; Septi Budi Sartika; Machful Indra Kurniawan; Siti Adira Salsabilla Rahma; Citra Azizah (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2026)
Enhancing higher order thinking skills (HOTS) in science education poses a difficulty due to the limitation of digital teaching resources focused on local environmental issues that facilitate students’ abilities in analysis (C4), evaluation (C5), and creation (C6). The novelty in its examination of a digital textbook addressing the Jetis Sidoarjo batik waste issue as a contextual medium to enhance HOTS in the C4, C5, and C6 indicators. This research aims to evaluate the effectiveness of a digital science textbook based on Socioscientific Issues (SSI) in enhancing students’ HOTS. This research specifically examines: the validity of the SSI-based digital science textbook, the enhancement of students’ HOTS after using the digital textbook, and the disparities in student learning results between digital and conventional textbooks. This research uses a quasi-experimental approach with a nonequivalent pretest-posttest control-group design. The research instruments comprise a HOTS test, expert validation forms, and documentation of learning results. The findings indicate that the developed digital textbook has valid criteria and very high quality. The experimental class’ N-Gain score of 0.72 is in the high category, indicating that the use of digital textbook is effective in improving students’ HOTS. The experimental class showed higher improvements than the control class in the C4, C5, and C6 indicators. The integration of the Jetis Sidoarjo batik waste issue encouraged students to actively analyze, evaluate, and propose solutions to environmental problems in their surrounding context. These findings suggest that SSI-based digital teaching materials can be an effective pedagogical alternative to facilitate contextual science learning and fostering HOTS.Abstrak. Penguatan keterampilan berpikir tingkat tinggi (HOTS) masih menjadi tantangan dalam pembelajaran IPA karena bahan ajar digital berbasis isu lingkungan lokal yang mengajarkan siswa pada proses analisis, evaluasi, dan kreasi masih terbatas. Kebaruan penelitian terletak pada pengujian buku ajar digital berbasis isu limbah batik Jetis Sidoarjo sebagai media kontekstual untuk meningkatkan HOTS pada indikator analisis (C4), evaluasi (C5), dan kreasi (C6). Tujuan penelitian ini adalah mengkaji efektivitas buku ajar digital IPA berbasis Socioscientific Issues (SSI) untuk meningkatkan HOTS siswa. Secara khusus, penelitian ini mendeskripsikan: validitas buku digital IPA berbasis SSI, peningkatan HOTS siswa setelah menggunakan buku digital, dan perbedaan hasil belajar siswa pada penggunaan buku digital dan buku teks konvensional. Penelitian ini menggunakan metode kuasi eksperimen dengan desain nonequivalent pretest-posttest control-group. Instrumen penelitian meliputi tes HOTS, lembar validasi ahli, dan dokumentasi hasil belajar. Hasil penelitian menunjukkan bahwa buku digital yang dikembangkan memenuhi kriteria valid dan memiliki kualitas yang sangat tinggi. Skor N-Gain kelas eksperimen sebesar 0.72 berada pada kategori tinggi yang mengindikasikan penggunaan buku ajar digital efektif dalam meningkatkan HOTS siswa. Kelas eksperimen menunjukkan peningkatan lebih tinggi dibandingkan kelas kontrol pada indikator C4), C5, dan C6.  Integrasi isu limbah batik Jetis Sidoarjo mendorong siswa untuk secara aktif menganalisis, mengevaluasi, dan mengusulkan solusi terhadap permasalahan lingkungan di sekitar mereka. Temuan ini menunjukkan bahwa bahan ajar digital berbasis SSI dapat menjadi alternatif pedagogis yang efektif untuk mendorong pembelajaran sains yang kontekstual dan mengembangkan HOTS siswa.